Bimetallic synergy in supported Ni–Pd catalyst for selective hydrogenolysis of C–O bonds in epoxy resins - Yanze Huang; Yukari Yamazaki; Katsutoshi Nomoto; Hiroki Miura; Tetsuya Shishido; Xiongjie Jin; Kyoko Nozaki (Nature Communications)
Abstract Recycling of epoxy composites is of importance for achieving circular economy as demand for lightweight materials in the field of sustainable technologies is soaring. Although catalytic hydrogenolysis of epoxy resins provides a promising approach to recover valuable fillers and phenolic compounds from the composites, there is a lack of a reusable solid catalyst for this purpose. Here, we report a robust CeO2-supported Ni–Pd bimetallic catalyst (Ni–Pd/CeO2) for the hydrogenolysis of C–O bonds in epoxy resins under 1 atm of H2. Benefiting from its heterogeneous nature, Ni–Pd/CeO2 can be reused for several times. Furthermore, the catalyst is successfully applied to decomposition of epoxy composites to recover carbon or glass fibers and phenolic compounds, implying the potential application of our catalyst system toward recycling of epoxy composites.